Drivers of Zillennial Customer Loyalty in Islamic Bank Mobile Banking: Evidence from BSI Mobile - Pratama, Ahmad Ilham; Susanto, Arnis Budi; Fatah, Abdul; Erlangga, Okyviandi Putra (Universitas Airlangga, 2024)
This research aims to tes and analyze service features, security and partial complant handling on customer satisfaction and loyalty of users of the BSI mobile gen-Z Students at Jember University. This research is in the form of explanatory research with a quantitative approach method. The data collection technique uses a questionnaire with accidental sampling as the sample technique. The population in this study were all BSI mobile gen-Z users students at the University of Jember and the sample in this study consisted of 100 respondents. Meanwhile, the data analysis technique uses path analysis with the IBM SPSS Statistics application. The results of this study indicate that service features have a positive and significant effect on customer satisfaction, security does not affect customer satisfaction, and complaint handling has a positive and significant effect on customer satisfaction. Service features do not affect customer loyalty, security does not affect customer loyalty, complaint handling has a positive and significant effect on customer loyalty, and customer satisfaction does not affect the loyalty of BSI mobile application users among Generation Z students at the University of Jember